The effect of hypoxic training on the enzymes AST, ALT, CPK and shooting precision for basketball players - Islam Ahmed Gomaa (Turkish Journal of Kinesiology, 2019)
The aim of this study is the impact of training on Hypoxic enzyme ALT, AST, CPK and Shooting precision for a basketball player. Applied study on a sample of 12 players from the basketball Players team in Cabsy Club in Port Said, Registered Egyptian Federation of Basketball/Egypt of the season 2015/2016, the researcher used experimental method to design two groups; one experimental consisted of 6 players and the other control group of 6 players. Where the average age of 23.33 ± 1.03 years and height 190.67 ± 4.76 cm, weight 97.50 ± 6.72 kg and age training 14.00± 1.10 month for the experimental group, while the average age 23.67 ± 0.52 years, height 191.00 ± 3.35 cm, weight 94.17 ± 7.31 kg and age training 14.50 ± 0.55 month for the control group. The experimental group underwent a Hypoxic Training program while the control group underwent Traditional exercises.  Researcher to conduct tests and measurements derived: measuring both lengths is converted Ristamiter device, body weight, the measurement of the rate of enzymes ALT, AST, CPK under discussion by pulling the blood samples of the sample and analyzed the laboratory in Port Said through laboratory reagents, measurement of tripartite Shooting precision, the measurement of near shooting precision. Hypoxic Training program: The program includes training the Pilot Group on a group of Hypoxic training for 12 weeks at a rate 4 training modules in the week, the total number of training modules in the program 48 Training Unit. The program includes the control group on traditional training in addition to warm up and pacification. The statistical analysis of the control and experimental data SPSS was used to apply formulas statistical by calculating: average, standard deviation, volume of effect size, Mann-Whitney and Wilcoxon test. The results showed the use of hypoxic training resulted in an improvement statistically significant at a level of Enzyme ALT, AST, and CPK for basketball players. The use of hypoxic training resulted in an improvement statistically significant shooting near and shooting triple precision for basketball players. These results should be taken into account by the basketball Federation and attention by coaches trained in the application of hypoxic training basketball players programs given the positive impact on the players.